Building the Capacity and Knowledge about Coral Rehabilitation of Tour Guides in Lemukutan Island - Dahlia Wulan Sari; Achis Martua Siregar; Tia Nuraya; Elliska Murni Harfinda; Mordik Erdiansyah (MITRA: Jurnal Pemberdayaan Masyarakat, 2021)
The coral reef ecosystem is one of the marine tourism attractions on Lemukutan Island, West Kalimantan. However, currently, some locations are in a relatively degraded condition, which should be addressed. One solution to this problem is coral transplantation activities involving tour guides. As part of the effort to rehabilitate the coral reef habitats, the Aquatic Resource Management Department, Faculty of Agriculture, Nahdlatul Ulama University, West Kalimantan, conducted community development activities to increase the capacity and knowledge of tour guides regarding coral reef ecosystems and coral transplantation techniques. This training was attended by fifteen tour guides from the Lemukutan Guide Group and ARTUNA (Anak Remaja Teluk Cina) Group. The participants were previously trained under PT Pertamina (Persero) and Yayasan Jejak Pesisir Nusantara. This training was carried out in three stages: (i) materials presentation and discussions, (ii) direct practice on the field, and (iii) evaluation. The post-test results showed that the training had increased participants' understanding of coral reef ecosystems and coral transplantation techniques by 40,00% and 33,33%, respectively.